Household Production Satellite Account as an Integral Account for Estimating Value Added in the National Economy - Marszałek, Marta (Rachunek satelitarny produkcji domowej jako trwały element szacunku wartości dodanej w gospodarce, 2025)
Aim: Satellite accounts provide an integrated economic framework that complements the System of National Accounts (SNA) by capturing economic activities not fully represented in core statistics. This study presents the Household Production Satellite Account (HPSA) as an example of best practices in extending official statistics. The primary goal is to estimate the monetary value of domestic work and household production (market and non-market) in Poland, contributing to an extended GDP model. Methodology: Following the ESA 2010 methodology, this study applies the input and replacement cost methods to assess unpaid labour, using the specialist wage approach to estimate housework value. Results: In 2023, Poland’s GDP was PLN 3,410.1 billion, with non-SNA household production account-ting for additional 46.5% to GDP. The value of domestic labour was PLN 1,605.9 billion, representing 79.9% of non-market household production. When using an extended economic framework, house-hold production constituted 34.6-36.5% of the national economy. Implications and recommendations: The results highlight the substantial contribution of household production, often overlooked in economic assessments. Regular valuation of satellite accounts, as re-commended by Eurostat and UNECE, would improve economic analysis. Integrating these accounts into national statistics provides a more comprehensive view of household contributions, reducing distortions in economic indicators. Originality/value: The most anticipated outcome of the analysis was the estimation of the gross value added of non-market household production and its comparison to the GDP for the total national economy across from 2003 to 2023.
Econometrics = Ekonometria, 2025, Vol. 29, No. 1, s. 1-14
Keywords: household production; input method; satellite accounts; time use survey; unpaid work; produkcja domowa; rachunki satelitarne; budżet czasu ludności; metoda nakładu; nieodpłatna praca domowa